Do mothers enjoy playing sensitively with their infants?. (27th May 2018) - Goldwater-Adler, Samantha; Wozney, Lori; McGrath, Patrick J.
Abstract: Background: Early sensitive caregiver–infant interactions form an important foundation for infant development. Although mutual enjoyment is thought to motivate proximity and continued interactions, there is no empirical evidence that mothers enjoy interacting and behaving sensitively. Research to date has focused on the influence of stable / pathological maternal negative emotions on parenting, with parenting often assessed on one occasion only. Therefore, little is known about what accounts for the variability in sensitivity across interactions. Objectives: The objective of the present study was to evaluate what makes sensitivity reinforcing to typical mothers and thus more likely to be repeated. We hypothesised that 15- to 28-week-old infants' positive and active engagement would mediate the relationship between their mothers' sensitivity and change in emotion state from pre- to post-interaction. Method: Using a naturalistic, repeated-measures design, 390 unique interactions from 49 mothers (mean age: M = 29.90 years, SD = 5.41) and their infants (25 female; mean age: M = 22.53 weeks, SD = 3.77) were rated using the Global Rating Scales of Mother–Infant Interaction. Mothers completed measures of their own mood (Profile of Mood States – 15) before and after each interaction. Results: Mothers reported feeling slightly less negative and more vigorous after interacting with their infants. The more sensitively they behaved, the more engaged their infants were and the more vigorous the mothers felt thereafter. Infant engagement did not mediate the relationship between sensitivity and change in negative emotion or in vigour. Conclusions: Results suggest that upon behaving sensitively, mothers feel more vigorous regardless of their infants' engagement.